Desarrollo de un Sistema de Indicadores de Sostenibilidad Ambiental para la Parroquia Guaytacama, Cantón Latacunga – Provincia de Cotopaxi. - Chacón Fuentes, Katherine Fernanda (2022)
This project established the development of a system of environmental sustainability indicators for the Guaytacama parish, Latacunga canton, Cotopaxi province, in which information was collected to identify the state of the ecosystems in the study area, as well as to analyze the incidence of existing environmental problems, their progress and the effects they cause on the Sumak Kawsay. The main objective was the development of environmental sustainability indicators to ensure the proper use of natural resources within the parish, focusing on the four main components which are human activities, water, soil and waste, because they constitute an optimal sustainable development system for the study area, which will allow the inhabitants and members of the Autonomous Decentralized Parish Government to evaluate the progress of sustainable and socio-environmental development, keeping as main regulations to follow the Environmental Regulations respectively. For the collection of information, a qualitative approach methodology was used, and at the same time the computer package Atlas Ti was used, starting with interviews with six leaders of the Guaytacama parish, providing in its response specific information on the existing reality of environmental problems and the little knowledge of the study area. Once the phenomena were recognized, the search for and development of indicators focused on the four components mainly affected, which is why for the project a total of 40 sustainability indicators were obtained, determining as a result 10 indicators for human activities, which will improve the areas of health, employment, tourism, education, etc. 10 indicators were selected for water resources, providing solutions to improve water quality, irrigation and contamination respectively; 8 indicators were also developed for soil resources based on the main environmental problems related to contamination, erosion and risk of desertification; and finally, 12 indicators were chosen for waste, which will promote and define the strategies on the action plan, thus determining preventive and corrective measures, in this way the project established in the development of environmental sustainability indicators in order to improve the existing problems of the selected components in the parish to promote a sustainable, friendly and ecologically balanced development respectively.